Mitigating Risks in Small Tourism Business: A Qualitative Study on Financial, Operational, Market, and Regulatory Challenges - Wulandari, Wisi; Aldora, Mega; Elmia, Arini Shofi; Sari, Pita Ratna; Ramadhania, Tiffany Chairunnisa (Integrasi Sains Media, 2025)
The tourism industry is a rapidly growing sector that significantly contributes to economic development, particularly through small tourism businesses. However, these businesses face various risks, including economic uncertainty, natural disasters, regulatory changes, and fluctuations in tourist demand. This study aims to analyze risk management strategies employed by small tourism enterprises to enhance their sustainability and competitiveness. Using a qualitative approach, the research explores various risk mitigation practices, such as financial management, service diversification, and adopting digital technology in business operations. Findings indicate that the ability of small tourism businesses to manage risks effectively depends on the owners' preparedness to identify and address potential threats. Key challenges include limited access to capital, informal business management, and inadequate financial record-keeping, often hindering long-term growth. To overcome these challenges, businesses adopt strategies such as improving financial literacy, implementing structured operational procedures, and leveraging digital marketing tools. Moreover, government support in the form of simplified licensing processes, financial training programs, and tourism promotion initiatives plays a crucial role in strengthening small tourism enterprises. This study contributes to the existing literature by offering empirical insights into small tourism businesses' practical risk management approaches. The proposed conceptual framework is a foundation for future quantitative research, enabling further examination of the relationships between risk factors, mitigation strategies, and business performance. By implementing structured risk management practices, small tourism businesses can enhance their resilience, sustain growth, and remain competitive in the evolving tourism industry.